Massilia rhizosphaerae sp. nov., a rice-associated rhizobacterium with antibacterial activity against Ralstonia solanacearum. Issue 9 (14th September 2021) - Li, Chenxu; Cao, Peng; Du, Chuanjiao; Zhang, Xue; Bing, Hui; Li, Lei; Sun, Peng; Xiang, Wensheng; Zhao, Junwei; Wang, Xiangjing
Abstract : A novel rhizobacterium, designated strain NEAU-GH312 T, with antibacterial activity against Ralstonia solanacearum was isolated from rhizosphere soil of rice (Heilongjiang Province, PR China) and characterized with a polyphasic approach. Cells of strain NEAU-GH312 T were Gram-stain-negative, aerobic, non-spore-forming, motile with peritrichous flagella and rod-shaped. Colonies were light orange, convex and semi-translucent on Reasoner's 2A (R2A) agar after 2 days of incubation at 28 °C. Growth was observed on R2A agar at 10–40 °C, pH 4.0–8.0 and with 0–5 % (w/v) NaCl. The respiratory quinone was ubiquinone Q-8. The major cellular fatty acids of strain NEAU-GH312 T were C16 : 1 ω 7 c and/or C16 : 1 ω 6 c, C16 : 0 and C18 : 1 ω 7 c and/or C18 : 1 ω 6 c . The main polar lipids were phosphatidylglycerol, phosphatidylethanolamine and diphosphatidylglycerol. Phylogenetic analyses confirmed the well-supported affiliation of strain NEAU-GH312 T within the genus Massilia, close to the type strains of Massilia arvi THG-RS2O T (98.7 %), Massilia norwichensis NS9 T (98.7 %) and Massilia kyonggiensis TSA1 T (98.6 %). Strain NEAU-GH312 T had a genome size of 6.68 Mb and an average DNA G+C content of 66.3 mol%. Based on the genotypic, phenotypic and chemotaxonomic data obtained in this study, strain NEAU-GH312 T could be classified as representative of a novel species of the genus Massilia, for which the name Massilia rhizosphaerae sp. nov. is proposed, with strain NEAU-GH312 T (=DSM 109722 T =CCTCC AB 2019142 T ) as the type strain.